Wali Mujbir dan Kebebasan Memilih Pasangan Bagi Perempuan Persepektif Ulama Kontemporer dan Fiqh Klasik - Muchlis Muchlis (HKI IAI Miftahul Ulum Pamekasan, 2022)
Marriage is a sacred activity that binds men and women in a family bond called a contract. Of course, dealing with it also really needs strengthening of heart and mind in order to create a lasting marriage and intertwined sakinah family, mawaddah warohmah. Including the requirements of pillars that must be met in marriage, namely the guardian of the woman, basically the guardian has the right of ijbar to his daughter (Imam Syafi'i) but this remains within the requirements that must be met and does not differ from the criteria determined by Islam. However, in context, today's women are starting to be reluctant to be forced into marriage by their guardians due to the progress of the globalization era. So that many guardians' ijbar rights in marriage have not been realized on the pretext that the daughter couple is happy with the candidate they choose. So in this case there is a very dynamic difference between madhhab priests and contemporary scholars, this is due to the emergence of a misalignment of khitob propositions against generality which occurs especially in this technologically advanced era when dealing with the arguments of the hadith of the Prophet Muhammad.